MONITORING AND CHARGING OF WHEELCHAIR BATTERIES BASED ON INTERNET OF THINGS (IOT) - HASSAN, AHMAD AIMAN (2018)
The prototype for monitoring and charging the wheelchair batteries based on Internet of Things has been designed. The prototype consists of the Arduino UNO as the main controller of the prototype, the voltage measurement unit to measure the Open Circuit voltage of the battery by using the voltage divider, modified extension with solid – state relay unit to control the charging of the wheelchair battery by connecting and disconnecting the electric supply to the battery charger, the Blynk application to display the data and control the charging of the wheelchair battery and ESP8266 WiFi module for wireless connection between the hardware and the Blynk application via the internet. The prototype is tested for the voltage measurement, wireless control of the modified extension and solid – state relay unit using Blynk application and display the measured data on the Blynk application. The result shows that the prototype can give adequate voltage measurement, able to control the modified extension and solid – state relay using Blynk application and show the measured voltage on the application. Thus, the project able to achieve its objective of monitoring and charging of the wheelchair battery based on Internet of Things.